Studying the association between cigarette smoking and serum copper, zinc, and magnesium concentrations: A cross-sectional study - Asmaa Mahmoud Mohammed; Adel F Hashish; Gamila S El-Saeed (Wolters Kluwer Medknow Publications, 2023)
Background and Objectives: Tobacco smoking causes damages almost for every organ in the body. Based on the literature review, the relationship between smoking, including nicotine dependence, and the serum zinc (Zn), copper (Cu), magnesium (Mg) status has not been studied sufficiently. The aim of the present study was to determine the relationship of cigarette smoking, including the nicotine dependence state of the smokers, with serum Cu, Zn, and Mg concentrations. Subjects and Methods: Overall, 41 active smokers and 44 nonsmokers were investigated for serum Cu, Zn, and Mg concentrations; in addition to urinary cotinine/creatinine ratio. The eight-item Fagerstrom test for nicotine dependence (FTND) questionnaire has been used to determine the nicotine dependence status of the smokers. Results: A significant hypozincemia has been detected in 34.1% of the smokers versus 9.1% of nonsmokers, with a five-fold higher risk than nonsmokers. Moreover, a significant hypomagnesemia has been detected in 24.4% of the smokers, with 6.7 fold higher risk than the nonsmokers. The serum Cu concentrations of the smokers were significantly higher (102.4 ± 17.5 μg/dl) than the nonsmokers (70.7 ± 17.1 μg/dl), (P < 0.0001). Each 1 year decrease in the initial age of starting smoking was associated with an increase in the serum Cu concentration by 0.016 μg/dl. Each increase in the serum Cu concentration by 1 μg/dl was associated with a decrease in the serum Zn and Mg concentrations by 0.4 μg/dl and 4 μg/dl, respectively. Conclusion: Cigarette smoking is a significant risk factor for hypozincemia, hypomagnesemia, and high Cu concentrations regardless of the nicotine dependence status of the smokers. Early management of hypozincemia may be a preventive measure to decrease the incidence of the oxidative stress-induced diseases.